Current application situation and developments of low-cost sand proppant in China. Issue 1 (September 2020) - Zheng, Xinquan; Wang, Xin; Liang, Tiancheng; Yang, Nengyu; Cai, Bo; Meng, Chuanyou; Fu, Haifeng
Abstract: Since 2014, the petroleum companies in North American have adopted self-operated and self-supplying modes to cut costs for proppants, such as replacing ceramic with sand and building sand plants nearby, achieving win-win results of continuous growth in oil and gas production and economic benefits. Enlightened by such situation in North America, in this study, the feasibility of sand promotion is demonstrated systematically in terms of the basic theoretical research, experimental testing and field tests. The research results indicate that: (1) the sand currently used in China can completely meet unconventional reconstruction requirements, as it has a crushing resistance grade equivalent to that of the yellow sand from the U.S. and the crushing rate and flow conductivity basically close to those of such yellow sand; (2)based on the characteristics of unconventional petroleum reservoirs and fluids and the differences between their completion modes and those of conventional petroleum reservoirs, the beneficial development of unconventional petroleum that can be realized by increasing the laying concentration and using the sand with small particle sizes has been verified; (3) the development potential of Shixi, Jiangyou, Yiliang and Chuxiong is demonstrated by conducting the localization feasibility study of sand sources to lay the foundations of further cost cutting and efficiency enhancement for unconventional petroleum; (4) the field tests have indicated that, in China, the sand used for fracturing can fully meet the technical demands of the reconstruction for unconventional reservoirs not deeper than 3, 500 m and shows good production effect and economic efficiency. In view of these research and understanding, the cost cutting of sand for more benefits shall be further enhanced to ensure the low-cost petroleum development in China. Specifically, the promotion and application of sand and building sand plants nearby shall be strengthened.